A platelet-cloaking tetramethylprazine-loaded microemulsion for improved therapy of myocardial ischaemia/reperfusion injury. (3rd July 2022) - Zuo, Zhi; Li, Menghuan; Han, Tao; Zheng, Xuhui; Yao, Wenming; Wang, Hui; Li, Xinli; Qu, Ding
Abstract: Myocardial ischaemia-reperfusion injury (MI/RI) induces injury against cardiomyocytes and triggers myocardial infarction. Previously, we demonstrated that tetramethylprazine (TMP) was a promising therapeutic agent for attenuating MI/RI. However, poor absorption and low homing efficiency are two main obstacles to the further application of TMP. In this study, a platelet membrane-cloaking TMP-loaded microemulsion (P/TMP-MEs) capable of promoting in vivo absorption and decreasing non-targeted accumulation was fabricated for the improved MI/RI therapy. The average particle size and zeta potential of P/TMP-MEs were 35.9 ± 2.5 nm and −29.4 ± 3.1 mV, respectively. 35.4 ± 2.4 wt% TMP was released from P/TMP-MEs after 48 h of incubation with rat plasma. The coating of the platelet membrane significantly decreased the internalisation of P/TMP-MEs by THP-1 macrophage-like cells compared with the non-platelet modified TMP-loaded microemulsion (TMP-MEs). Besides, P/TMP-MEs did not activate the complement system. After treatment with P/TMP-MEs, the dehydrogenase (LDH) level of the cardiomyocytes was significantly lower than other controls. Rats single-administrated with P/TMP-MEs exhibited the area under the plasma concentration-time curve (AUC) at 463796.7 ± 53614.3 ng/mL/h, and ∼400 ng/mL TMP could still be detected from the plasma after 24 h of administration, exhibiting a prolonged blood circulation time as the platelet membrane coating. More importantly, in the MI/RI therapy in vivo, the creatine kinase (CK) and LDH of the rats treated with P/TMP-MEs were remarkably decreased compared with the free TMP and TMP-MEs groups. The combinational strategy of platelet membrane coating and microemulsion assembly endows TMP with a better prospect for MI/RI therapy.